Alat Pendeteksi Kesalahan Pembacaan kWh Meter 1 Fasa dengan Notifikasi SMS disertai Lokasi - Sumanto, Azzahra; Chusna Arif , Yahya; Dwitya Nugraha, Syechu (ENERGI & KELISTRIKAN, 2024)
In the implementation of electricity energi transactions, it is important to accurately record the amount of electricity consumed by customers. One possible error that can occur in kWh meters is non-technical power loss, where the recorded energi is lower than the actual energi used by customers. This issue has detrimental impacts on companies in the electricity business, leading to the implementation of Electricity Usage Regulation (P2TL) activities on customer kWh meters. The objective of this research is to design a single-phase kWh meter reading error detection tool to identify anomaly in kWh meters. The tolerance limit for measurement error used is ±1% in accordance with Class 1.0 kWh meters. The research methodology includes literature studies, prototype system design, partial testing, and overall system integration testing. The test data results from this research show a deviation of 0.76% for kWh meters with standard wiring, while kWh meters with non-standard wiring exhibit a deviation of 45.84%. In the system for reading errors in single-phase kWh meters, the measured power values are displayed on an LCD screen, and the system also sends SMS notifications.